2008
DOI: 10.1016/j.neuroscience.2008.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Acute nicotine activates c-fos and activity-regulated cytoskeletal associated protein mRNA expression in limbic brain areas involved in the central stress-response in rat pups during a period of hypo-responsiveness to stress

Abstract: In adult rats, acute nicotine, the major psychoactive ingredient in tobacco smoke, stimulates the hypothalamic-pituitary-adrenal axis (HPA), resulting in activation of brain areas involved in stress and anxiety-linked behavior. However, in rat pups the first two postnatal weeks are characterized by hypo-responsiveness to stress, also called the 'stress non-responsive period' (SNRP). Therefore, we wanted to address the question if acute nicotine stimulates areas involved in the stress response during SNRP? To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
0
5
1
Order By: Relevance
“…These genes have been implicated in synaptic plasticity [ 115 ] and associated with addiction [ 113 ]. Our results are not consistent with previous research that has reported increased Arc and Fos expression in the prefrontal cortex (PFC) following an acute injection of nicotine in adolescent male rats [ 113 ] and rat pups [ 116 ]. It is possible that we observed a different pattern of gene expression due to the brain region studied.…”
Section: Discussioncontrasting
confidence: 99%
“…These genes have been implicated in synaptic plasticity [ 115 ] and associated with addiction [ 113 ]. Our results are not consistent with previous research that has reported increased Arc and Fos expression in the prefrontal cortex (PFC) following an acute injection of nicotine in adolescent male rats [ 113 ] and rat pups [ 116 ]. It is possible that we observed a different pattern of gene expression due to the brain region studied.…”
Section: Discussioncontrasting
confidence: 99%
“…respectively, which also can be evaluated in animal models (Lara et al�, 2006)� Dysfunction in the monoamine systems, in particularly the noradrenergic, dopamineric and serotonergic systems, has been strongly implicated in affective disorders including anxiety, depression and aggression (van Praag, 1998;Ressler & Nemeroff, 2000;Nutt, 2006;Seo et al�, 2008;Goddard et al�, 2010), and make individuals susceptible to subsequent substance abuse, as well as increase risk of posttraumatic stress disorder, major depressive disorder and suicide� There is strong evidence to suggest that gestational exposure to nicotine affects the development of central monoamineric systems in rodents (Muneoka et al�, 1997;Slotkin et al�, 1987;Oliff & Gallardo, 1999;Xu et al�, 2001)� Furthermore, in young postnatal rat pups, a period that corresponds to the third trimester of human development (Winzer-Serhan, 2008), nicotine specifically activates brain areas involved in the central stress response pathway including the noradrenergic locus coeruleus (Schmitt et al�, 2008)� Thus, it is possible that gestational exposure to nicotine due to maternal smoking affects normal development of monoaminergic transmitter systems, which could constitute a major underlying cause for the affective behavioral abnormalities seen in people whose mother smoked while pregnant�…”
Section: Long-term Effects Of Developmental Nicotine Exposure On Anximentioning
confidence: 99%
“…The relationship between smoking and headache is controversial (28). A possible mechanism of headache in smokers with pituitary adenoma might be based on the central effects of nicotine: Acute exposure to nicotine results in an increase of ACTH, PRL (29) and hGH (30) and in an increase of sleep-onset latency (31). In rats, this influence on the hypothalamus-pituitary adrenal axis and on the control of endogenous rhythms and sleep architecture is mediated by brainstem catecholaminergic neurons with a subsequent noradrenaline release in the hypothalamic paraventricular nucleus (32).…”
Section: Mechanical Factorsmentioning
confidence: 99%